State Power and Borderlands: Costa Rican North Region, Looked by Through Road Projects in Second Half 20th Century - Villalobos Cubero, Lissy Marcela (Revista de historia., 2021)
This paper is studies how the Costa Rican state still sought, in the second half of 20th century, to incorporate the northern region into projects emanating from the center of the country. Road projects are taken as a common thread, revealing the dimensions of intra and inter-regional territorial links, in a context of Cold War and political instability in Central America, which made these border areas spaces of great dynamism and some change. The census maps (1973 and 1984) were main sources for reconstruction communication networks, during that decades.